The responses of the Gauteng Department of Social Development to homelessness during the COVID 19 lockdown: A case study of two Tshwane and Johannesburg homeless shelters - Ngcobo, Noluthando (University of the Witwatersrand, Johannesburg, 2024)
How homelessness presents itself in Gauteng is complex and to dissect this phenomenon, the study undertook to explore the responses and approaches to homelessness during the COVID 19 pandemic and from these, establish how the department conceptualizes homelessness, what policies informed the approaches, and lastly, explore whether these interventions were successful or not. Having used document analysis and semi-structured interviews with social workers, the study made key recommendations for the DSD to take into consideration for future interventions. Of great concern is the lack of policy and a legislative framework that guide strictly the DSD’s interactions with homeless people. The study further found that factors including unemployment, migration and urbanisation, and substance abuse are structural factors that attribute to the persistent nature of homelessness in Gauteng. If the DSD seeks to truly eradicate homelessness, the study recommends that more resources need to be invested into sustainable interventions, improving intergovernmental relations as the problem is greater than the confines of the department, and developing solid policy and legislation.
A research report submitted in fulfillment of the requirements for the Master of Arts, In the Faculty of Humanities, School of Social Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Homelessness; Department of Social Development; COVID 19 Lockdown; SDG-3: Good health and well-being; SDG-11: Sustainable cities and communities